2007
DOI: 10.3748/wjg.v13.i39.5245
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous cervical esophagus ultrasound in adults: Relation with ambulatory 24-h pH-monitoring and esophageal manometry

Abstract: AIM:To determine the gastroesophageal refluxate in the cervical esophagus (CE) and measure transcutaneous cervical esophageal ultrasound (TCEUS) findings [anterior wall thickness (WT) of CE, esophageal luminal diameter (ELD), esophageal diameter (ED)]; to compare TCEUS findings in the patient subgroups divided according to 24-h esophageal pH monitoring and manometry; and to investigate possible cut-off values according to the TCEUS findings as a predictor of gastroesophageal reflux (GER). METHODS:In 45/500 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
(77 reference statements)
0
11
0
Order By: Relevance
“…Chen et al [27] and Zhu et al [28] both showed that the normal cervical wall thickness was between 1.8 and 2.3 mm. Kacar et al [8] reported the left anterior wall thickness as 2.29 8 0.38 mm (1.57-4.0) and they found no difference between GER-and GER+ subjects. However, we found a statistically significant difference between GER-and GER+ children with respect to anterior WTCE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chen et al [27] and Zhu et al [28] both showed that the normal cervical wall thickness was between 1.8 and 2.3 mm. Kacar et al [8] reported the left anterior wall thickness as 2.29 8 0.38 mm (1.57-4.0) and they found no difference between GER-and GER+ subjects. However, we found a statistically significant difference between GER-and GER+ children with respect to anterior WTCE.…”
Section: Discussionmentioning
confidence: 99%
“…Kacar et al [8] reported the cervical anteroposterior esophageal diameter as 5.5 8 12.4 mm and found no difference between GER+ and GER-subjects. We compared UED between GER-and GER+ children, and conversely we found a statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…hiatus hernia, malrotation) [8] along with the valuable experiences that practitioners have acquired through the years since the 1980s, ultrasonography (US) has been used as an alternative to BS in the diagnosis of GERD [9]. Esophageal US has been described as a noninvasive, readily available, repeatable, cheap, and fast technique that could be commonly used in the diagnosis and follow-up of young children with GERD [10][11][12][13][14][15]. Comparative studies of transabdominal US and BS demonstrated that US presents a higher sensitivity in the diagnosis of GERD [16,17].…”
Section: Introductionmentioning
confidence: 99%